2016
DOI: 10.1088/0952-4746/36/4/922
|View full text |Cite
|
Sign up to set email alerts
|

In-field evaluation of the impact of ageing and fading effects on annual radon concentration measurements for two different techniques

Abstract: Measurements covering a 1 year period are often used and required by legislation to assess the average radon concentration within a house or a workplace. This kind of long-term measurement-generally carried out with techniques based on nuclear track detectors-can be affected by a reduction in sensitivity due to ageing and fading of latent tracks during the exposure period, thus resulting in an underestimation of the actual average concentration. In order to evaluate in field conditions the ageing and fading ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also, Franci et al (2015) found that the sensitivity of CR-39 detectors (manufactured by Radosys, Ltd) continuously exposed in a reference radon chamber at room temperature over 3 and 6 months reduced by 4 and 7.5%, respectively. Recently, Venoso et al (2016) carried out a study to evaluate both the average and the variability of ageing and fading effects in real conditions, by using CR-39 (Radosys, Ltd.) and LR115 (Kodak) passive devices. In case of CR-39, radon annual average values estimated over a 12-month long period were found on average 16% lower than those estimated with two consecutive 6 months samplings.…”
Section: Effect Of Long-time Sampling -Analysis Of Results Of Test 1 and Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Franci et al (2015) found that the sensitivity of CR-39 detectors (manufactured by Radosys, Ltd) continuously exposed in a reference radon chamber at room temperature over 3 and 6 months reduced by 4 and 7.5%, respectively. Recently, Venoso et al (2016) carried out a study to evaluate both the average and the variability of ageing and fading effects in real conditions, by using CR-39 (Radosys, Ltd.) and LR115 (Kodak) passive devices. In case of CR-39, radon annual average values estimated over a 12-month long period were found on average 16% lower than those estimated with two consecutive 6 months samplings.…”
Section: Effect Of Long-time Sampling -Analysis Of Results Of Test 1 and Testmentioning
confidence: 99%
“…In the second "International radon in-field intercomparison for passive measurement devices: dwellings and workplaces" the attention was focused on different issues potentially affecting the quality of radon concentration measurements in real situations. In particular, the effect of long time sampling at low and high radon levels (fading) (Caresana et al, 2010;Venoso et al, 2016) and the effect of the simultaneous presence of radon and thoron (Sumesh et al, 2013;Tokonami et al, 2008). In order to provide reliable reference values of the activity radon concentration, before the intercomparison started, particular attention was paid to metrological issues as the determination of the intrinsic background of radon active monitors, to their calibration and to the evaluation of the influence of thoron in radon active measurements.…”
Section: Introductionmentioning
confidence: 99%